Valence attacks harm the electoral performance of the left but not the right - Jung, JH; Tavits, M (University of Chicago Press, 2020)
During election campaigns, parties attack each other’s non-ideological traits such as competence and integrity. However, it is unclear to what extent valence attacks reduce voter support for the target party. Drawing from theories on left-right personality and associated cognitive flexibility, we argue that valence attacks harm the electoral performance of leftist but not rightist parties. The relative openness of leftist voters makes them more willing to accept negative information about their party and act upon it. In contrast, the relative closedness of rightist voters makes them less likely to reconsider their political preferences in the face of negative information. We find robust evidence for our argument at the aggregate and individual levels using original data on media coverage of party campaigns in 10 European countries. We also provide experimental evidence in support of our argument. The findings have important implications for research on non-ideological rhetoric in party competition.